Harnessing Water Resources in Nepal: Flood Control to Hydro power Development - Thanju, Jeewan Parsad (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
DOI: http://dx.doi.org/10.3126/hn.v13i0.9663